Pragmatic value of noun phrase and verb phrase ellipsis in corporate communication - Elena N. Malyuga; Olga A. Dzhagatspanyan (Training, Language and Culture, 2024)
Although ellipsis has been extensively researched in theoretical linguistics, the pragmatic applications of ellipsis in corporate interactions remain largely unexplored. While previous studies have empirically established that the omission of noun phrases (NPE) and verb phrases (VPE) serves to economise and facilitate communication and create a different interpretation for the recipient, little is known about the pragmatic functions of these elliptical constructions within a corporate context and how the pragmatics of NPE and VPE can help contribute to achieving the communicative goals. The current study seeks to identify the pragmatic value of NPE and VPE in corporate communication in order to see how they contribute to the efficiency of the discourse and its emotional intensity. The study captures both qualitative and quantitative data. Data were gathered from 312 transcripts obtained from corporate communications (negotiations, meetings, presentations). During the qualitative phase, discourse analysis was used to analyse the function of NPE and VPE in achieving communicative functions such as clarity, emphasis, and rhetorical effect. For the quantitative phase, measuring the frequency of occurrence and contextual usage of these constructions contributed to discerning patterns and functions in the use of NPE and VPE in corporate discourse. Across both the qualitative and quantitative phases, results indicated that NPE and VPE improved discourse efficiency by eliminating redundancies and narrowing focus on strategic elements for an audience. It was additionally shown that NPE improved the emphasis on important content by eliminating redundancies while the use of VPE conveyed urgency and immediacy across communicative contexts. The quantitative phase also illustrated NPE and VPE as easily replicable constructs and that their strategic use influences an audience’s emotional reaction. Additionally, the analysis showed NPE and VPE may contribute to recipient’s perception of confidence and authority regarding their communicative competency in a corporate setting. The study thus challenges the traditional view of ellipsis from linguistic theory to be understood as a tool of pragmatics, not only for its ability to reduce language, but to direct attention and interpretation. The final conclusion of the research is NPE and VPE have specific value in building improved strategies of corporate communication, creating clarity, and emphasising information of importance.